Weeds Management In Organic Farming Through Conservation Agriculture Practices - Baral, Khagendra Raj (Journal of Agriculture and Environment, 2013)
Despite weeds are a serious threat to promotion of organic farming, relatively less attention is given to research on weed management. This article explores a scope of integration of conservation agriculture for weed control and soil protection under organic farming. Limitation in the use of agro-chemicals under OF promotes intensive tillage for weed control. Mostly, tillage leads to depletion of organic matter and proneness to erosion in inclined geography. Adoption of conservation agriculture reduces the intensity of soil manipulation thereby creates an unfavourable condition for weed seed germination, reduces the organic matter depletions and soil erosions. Residues on the surface invite weed and pest predators thereby reduced the weed and pest infestations in organic field. Appropriate crop rotations and cover crops management suppress weeds populations with smothering and allopathic effects. Thus, CA integration under OF could be an option for weed, pest and soil management which leads to sustainable organic plant production. The Journal of Agriculture and Environment Vol:13, Jun.2012, Page 60-66 DOI: http://dx.doi.org/10.3126/aej.v13i0.7589